J. VASSALLO - Seamless: Digital Collage and Dirty Realism in Contemporary Architecture - González de Canales, Francisco (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2017)
Jesús Vassallo Seamless: Digital Collage and Dirty Realism in Contemporary Architecture Architecture at Rice/Park Books, Houston y Zúrich, 2016, 208 páginas. Idioma: inglés. Tapa dura. 38 €. ISBN-10: 3038600199. ISBN-13: 978-3038600190